The Application of the Essence of the Suttas addressed by Venerable Sāriputta to Daily Life - Vudha, Eindar (The Journal of International Buddhist Studies College, 2021)
In Buddhism, there is threefold Piṭaka. Of this, there are many suttas from the disciples of the Buddha but here what this paper is going to discuss is to comprehend and apply the essence of the suttas in Majjhima Nikāya addressed by Venerable Sāriputta. Therefore, there will discuss the essential themes, unlocking the hidden meaning of a word from context and the application of them to daily life. This article also attempts to underline the salient features of the suttas that can promote the teachings of the disciple to be evident and obvious until becoming a Buddhist Role Model among the Buddhist people and societies after practicing and observing the genuine essence of the suttas from Venerable Sāriputta’s qualities of the personal examples.